2012
DOI: 10.1029/2011gc003934
|View full text |Cite
|
Sign up to set email alerts
|

The role of slabs and oceanic plate geometry in the net rotation of the lithosphere, trench motions, and slab return flow

Abstract: [1] Absolute plate motion models with respect to a deep mantle reference frame (e.g., hot spots) typically contain some net rotation (NR) of the lithosphere. Global mantle flow models for the present-day plate setting reproduce similarly oriented NRs but with amplitudes significantly smaller than those found in some high NR Pacific hot spot reference frames. It is therefore important to understand the mechanisms of NR excitation, which we attempt here with two-dimensional cylindrical models of an idealized Pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 89 publications
10
32
0
Order By: Relevance
“…Gérault et al . [] showed that in 2‐D cylindrical‐geometry simulations with free‐slip boundary conditions, the rate of lithospheric net rotation depends more strongly on properties of slabs, the location of ridges, and the coupling of plates at the trench (i.e., presence and properties of a weak zone) and less strongly on the presence of continental keels. Our 3‐D calculations use kinematically prescribed boundary conditions and consequently the locations and kinematics of plate boundaries, including trench migration, are not free parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gérault et al . [] showed that in 2‐D cylindrical‐geometry simulations with free‐slip boundary conditions, the rate of lithospheric net rotation depends more strongly on properties of slabs, the location of ridges, and the coupling of plates at the trench (i.e., presence and properties of a weak zone) and less strongly on the presence of continental keels. Our 3‐D calculations use kinematically prescribed boundary conditions and consequently the locations and kinematics of plate boundaries, including trench migration, are not free parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The role of slabs in generating net rotation in 3‐D spherical‐geometry flow models may be more limited than the 2‐D cylindrical geometry experiments of Gérault et al . [] suggest. Becker and Faccenna [] performed calculations in which lateral viscosity variations associated with slabs were incorporated using the slab model of Steinberger [] and found that the rate of net rotation produced by slabs was less than that produced in models that introduced continental keels, reaching only 10% of the HS3 rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of full spherical geometry is still computationally expensive, particularly if one wishes to accurately resolve mantle dynamics at the present‐day convective vigor of the Earth [ Stadler et al ., ]. The use of a cylindrical geometry [ van Keken , ; Gérault et al ., ] or other two‐dimensional approximations to the spherical Earth [ Hernlund and Tackley , ], where the models take into account at least in part the curvature of the Earth and the connectedness of the Earth mantle, are therefore still attractive options.…”
Section: Discussionmentioning
confidence: 99%
“…It is somehow equivalent to introducing a weak zone in numerical models that is used to mimic the effect of a fault subduction zone (e.g. Zhong and Gurnis, 1994;Gérault et al, 2012).…”
Section: Methodsmentioning
confidence: 99%